DETERMINASI PROFITABILITAS DI PT INKA (PERSERO) SEBELUM DAN SELAMA PANDEMI COVID-19 - Serdiliyani, Rochmanida Hana; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research was conducted to determine the effect of capital structure (DAR), leverage (DER), liquidity (CR), and research time dummy (Dwp) on the profitability (ROA) of PT INKA (Persero) quarterly in 2013 – 2021 with inflation (TI) as control variable. The purposive sampling method used is as many as 36 data which have been processed using the interpolation method. The data analysis technique uses multiple linear regression with a second difference. The results obtained from this study are (1) DAR has no significant effect on ROA, (2) DER has no significant effect on ROA, (3) CR has a positive and significant effect on ROA, (4) Dwp has a positive and significant effect on ROA, (5) Simultaneously DAR, DER, CR, and Dwp with TI as the control variable have a significant effect on ROA.